Reducing methane production from stored feces of dairy cows by Asparagopsis taxiformis - Ramin, Mohammad; Chagas, Juana C. C.; Pal, Yash; Danielsson, Rebecca; Fant, Petra; Krizsan, Sophie J. (Frontiers in Sustainable Food Systems, 2023)
The objective was to evaluate if methane (CH4) production from stored feces of cows previously supplemented with Asparagopsis taxiformis (AT) in their diet was lower compared with the feces of cows not supplemented with AT. We also investigated the possibility to further reduce CH4 production by adding AT to the stored feces of cows. Fecal samples were provided from a feeding trial (during two different periods) from four cows divided into two different groups. One group was supplemented with AT at a level of 0.5% of the total organic matter intake, and the other group was not supplemented with AT. A 2 × 2 factorial design was set in the laboratory for the incubation of feces. Fecal samples from the two groups of cows were each divided into two subsamples receiving either no addition of AT or addition of AT at a level of 0.5% of OM incubated. This resulted in four treatments with two replicates per period. The same design was repeated during period two. A total amount of 400g fresh fecal sample was incubated in 1-liter serum bottles for nine weeks at 39°C in a water bath. CH4 and total gas production were measured on day 1, 4, 7, and subsequently every second week until the end of the incubation period. Enteric CH4 production showed a significant reduction (61%) when AT was supplemented in the diet of dairy cows. CH4 production from feces of dairy cows supplemented with AT in their diet was only numerically lower (P = 0.61). Adding AT to the feces of dairy cows significantly reduced CH4 production from the feces by 44% compared to feces without AT. There were no differences observed in the bacterial and archaeal community profiles of fecal samples between cows fed AT and those not fed AT. The current study concludes that the addition of AT to stored feces can effectively reduce CH4 production from the feces of dairy cows.